Assessment of Diverse Pelvic Pain in the First Trimester of Pregnancy with Ultrasound Guidance - Muhannad Faleh Alanazi (AlQalam Journal of Medical and Applied Sciences, 2024)
Identifying and treating a pelvic pain during pregnancy can be challenging. Pregnant women still use ultrasound as their primary imaging modality. The current study set out to investigate the potential function of ultrasonography guidance in various pelvic pain sources during the first trimester of pregnancy. The Maternity and Children Hospital (MCH) and the Department of Radiology collaborated together to perform this cross-sectional descriptive study. 50 pregnant women, ages ranging from under 20 to over 30, who had pelvic pain throughout the first trimester (up to 12 weeks gestational age) participated in the study. All women had undergone clinical evaluations then to be referred for ultrasonography scans for the confirmation of diagnosis. SPSS software (version 25) was used to analyze the data and association using Odds ratio and multivariable logistic regression. In a study of 50 pregnant women with an assisted ultrasound. Among 22 (44%) and 28(56%) women were viable and non-viable pregnant. 60 percent of the women were primigravida, and 40 percent were multigravida. With a mean BMI of 28.7±4.21, the average age was 27.3±13.18 years. The most frequent causes of pelvic pain were abortion (22%), uterine fibroid (14%), and corpus luteal cyst (12%) in addition to Scar site pregnancy, Sub chorionic hematoma, ectopic pregnancy, and acute appendicitis were 8%,6%,6% and 1% respectively. whereas 30% of a normal pregnancy was found. The most reliable and non-invasive diagnostic technique for identifying various types of pelvic pain in pregnant women is ultrasound. It has been demonstrated that the timely treatment of women through the use of ultrasonography reduces the mortality rates linked with pregnancy problems. يمكن التعرف على آلام الحوض خلال فترة الحمل وعلاجها تحدياً. لا يزال النساء الحوامل يستخدمن الأشعة فوق الصوتية كوسيلة رئيسية للتصوير. تهدف هذه الدراسة إلى استكشاف الدور المحتمل لتوجيه الأشعة فوق الصوتية في مصادر آلام الحوض المتنوعة خلال الثلث الأول من الحمل. تعاون مستشفى النساء والولادة وقسم الأشعة لإجراء هذه الدراسة الوصفية. شارك في الدراسة 50 امرأة حامل، تتراوح أعمارهن بين أقل من 20 وأكثر من 30 عامًا، وكانت تعاني من آلام حوضية خلال الثلث الأول من الحمل (حتى الأسبوع 12 من العمر الجنيني). خضعت جميع النساء لتقييمات سريرية ثم تم إحالتهن لإجراء فحص الأشعة فوق الصوتية لتأكيد التشخيص. استخدم برنامج SPSS (الإصدار 25) لتحليل البيانات والعلاقات باستخدام نسب الاحتمال والانحدار اللوجستي متعدد المتغيرات. أظهرت الدراسة التي أجريت على 50 امرأة حامل مع مساعدة الأشعة فوق الصوتية وجود 22 امرأة (44٪) لديها الالم و28 امرأة (56٪) من غيرالالم. وكانت 60 في المائة من النساء حوامل لأول مرة، بينما كانت 40 في المائة منهن حوامل متعددة. كان متوسط مؤشر كتلة الجسم 28.7 ± 4.21، ومتوسط العمر 27.3 ± 13.18 عامًا. كانت أكثر الأسباب شيوعًا لآلام الحوض الإجهاض (22٪)، وورم الرحم الليفي (14٪)، وكيس الجسم الاصفر (12٪) بالإضافة إلى الحمل في موقع ندبة العملية القيصرية السابقة، والورم الدموي تحت المشيمة، والحمل خارج الرحم، والتهاب الزائدة الدودية الحاد وكانت نسبهم 8٪، 6٪، 6٪ و1٪ على التوالي. في حين تم العثور على 30٪ من الحمل الطبيعي. تعتبر فحوص الأشعة فوق الصوتية الأكثر موثوقية وغير مخترقة للجسم وآمنة في التشخيص والتحديد لمختلف أنواع آلام الحوض لدى النساء الحوامل. أظهرت النتائج أن العلاج والتشخيص المبكر للنساء باستخدام الأشعة فوق الصوتية تقلل من معدلات الوفيات المرتبطة بمشاكل الحمل